I need help solving this logarithmic equation: ln x + ln (x+3) = 1.

I know ln x + ln (x+3)=ln [x(x+3)] and that is ln x^2 + 3x when broken down. Then you have to get rid of ln by taking the natural base e of both sides so in the end you have x^2+3x = e^(1). That's when I got stuck.

2 answers

You are on the right track. Remember that e^1 = e = 2.718..
You just need to use the quadratric equation to solve
x^2 + 3x -2.718 = 0
since it cannot be factored easily.

x = [-3 +/- sqrt (19.87)]/2
= 1.458/2 or -7.458/2 = 0.729 or -3.729
x+5=4